The association of human leukocyte antigen alleles with clinical disease progression in HIV-positive cohorts with varied treatment strategies. (1st April 2021) - Ekenberg, Christina; Reekie, Joanne; Zucco, Adrian G.; Murray, Daniel D.; Sharma, Shweta; Macpherson, Cameron R.; Babiker, Abdel; Kan, Virginia; Lane, H. Clifford; Neaton, James D.; Lundgren, Jens D.
Abstract : Objectives: The Strategic Timing of AntiRetroviral Treatment (START) and Strategies for Management of Antiretroviral Therapy (SMART) trials demonstrated that ART can partly reverse clinically defined immune dysfunction induced by HIV replication. As control of HIV replication is influenced by the HLA region, we explored whether HLA alleles independently influence the risk of clinical events in HIV+ individuals. Design: Cohort study. Methods: In START and SMART participants, associations between imputed HLA alleles and AIDS, infection-related cancer, herpes virus-related AIDS events, chronic inflammation-related conditions, and bacterial pneumonia were assessed. Cox regression was used to estimate hazard ratios for the risk of events among allele carriers versus noncarriers. Models were adjusted for sex, age, geography, race, time-updated CD4 + T-cell counts and HIV viral load and stratified by treatment group within trials. HLA class I and II alleles were analyzed separately. The Benjamini--Hochberg procedure was used to limit the false discovery rate to less than 5% (i.e. q value <0.05). Results: Among 4829 participants, there were 132 AIDS events, 136 chronic inflammation-related conditions, 167 bacterial pneumonias, 45 infection-related cancers, and 49 herpes virus-related AIDS events. Several associations with q value less than 0.05 were found: HLA-DQB1*06:04 and HLA-DRB1*13:02 with AIDS (adjusted HR [95% CI] 2.63 [1.5–4.6] and 2.25 [1.4–3.7], respectively), HLA-B*15:17 and HLA-DPB1*15:01 with bacterial pneumonia (4.93 [2.3–10.7] and 4.33 [2.0–9.3], respectively), and HLA-A*69:01 with infection-related cancer (15.26 [3.5–66.7]). The carriage frequencies of these alleles were 10% or less. Conclusion: This hypothesis-generating study suggests that certain HLA alleles may influence the risk of immune dysfunction-related events irrespective of viral load and CD4 + T-cell count. Abstract : Supplemental Digital Content is available in the text